Identifying Sixth Grade Students’ Misconceptions on Solar System - Putri, Febiola Eka; Hermita, Neni; Zufriady, Zufriady; Wijaya, Tommy Tanu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to determine sixth grade students’ misconception on the solar system. This study uses a sampling technique with a total sample of 88 students. This research uses the descriptive quantitative method. This research aims to describe the misconceptions on the material of the solar system in class 6 of public elementary school in Pekanbaru, data collection techniques using the Four Tier Test. The results showed that students' misconceptions were categorized as